Evaluating Workplace Trust as a Construct of Worker Engagement in Construction. Issue 3 (21st February 2019) - Lawani, Kenneth; Hare, Billy; Cameron, Iain
Abstract : This qualitative study developed trust themes: 'lack of trust, ability (skill, experience and competence), benevolence and company integrity' from interviews based on the perceptions of workers. It also developed a framework which was used for validating workplace trust and its influence on Occupational Safety and Health (OSH) practices. The phenomenological study adopted semi-structured interviews involving engaged workers until saturation. Additional 22 workers participated in validating the trust framework. Findings suggest that no worker perceived lack of trust within their organisations. Two workers perceived their own skill, knowledge and experience and that of other workers to work safely (as far as level 2); but do not perceive their organisation to genuinely care or exhibit elements of company integrity. Six workers perceived the presence of ability and genuine benevolence qualities within their workplace (as far as level 3). However, they identified lack of company integrity from their managers or supervisors, and that management often not do what they say regarding OSH practices at all times. Fourteen workers perceived the presence of ability, genuine benevolence and company integrity qualities (as far as level 4), and that the management adhere to a set of principles that they find acceptable and consistent. These workers also perceive their workplaces to have a strong and transparent organisational leadership and integrity. This study of workplace trust is part of a wider study involving the development of a Worker Engagement Maturity Model and a prototype mobile digital tool which would be useful for assessing existing workforce engagement towards improving OSH practices.